2010
DOI: 10.1080/09540121.2010.484457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating counseling outcome on adherence to prophylaxis and follow-up after sexual HIV-risk exposure: a randomized controlled trial

Abstract: This study suggests the effectiveness of a counseling program to enhance adherence to both PEP and HIV testing follow-up after sexual exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
3
25
0
2
Order By: Relevance
“…In our study, only 56% of people who were prescribed a complete PEP treatment underwent HIV-testing follow-up at 8 weeks and 20% of those who stopped PEP because of low risk. These low percentages are consistent with previous findings in PEP studies [17, 18]. Besides PEP prescription, good follow-up was previously found associated with older age and sexual encounter with a sex worker [19].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, only 56% of people who were prescribed a complete PEP treatment underwent HIV-testing follow-up at 8 weeks and 20% of those who stopped PEP because of low risk. These low percentages are consistent with previous findings in PEP studies [17, 18]. Besides PEP prescription, good follow-up was previously found associated with older age and sexual encounter with a sex worker [19].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have also shown that adherence counselling and active tracing mechanisms can improve adherence and treatment outcomes, and can also reduce loss to follow up [18,19]. Alternatively, poor adherence among mothers' who initiated lifelong ART could be a reflection of their poor health status.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial from South Africa assessed telephonic psychosocial support, a leaflet and an adherence diary to support victims of sexual assault [12]; the two other randomized trials, conducted in France [13] and the United States [14], assessed counseling interventions to support nonoccupationalexposed cases. All three studies showed a tendency towards improved adherence to PEP, with an overall pooled odds ratio for improved adherence of 1.4 (95% CI 0.9-2.3%).…”
Section: Interventions To Support Adherencementioning
confidence: 99%